Pouring new wine into old wineskins how to change a church without destroying it - Malphurs, Aubrey (Grand Rapids, MI Baker, 1993)
Inlcudes bibliographical references and index.
Includes worksheets.
Keywords: Church growth; Change -- religious aspects -- Christianity